2019
DOI: 10.3389/fpsyg.2019.01323
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control Moderates the Relationship Between Exposure to Bullying Behaviors and Psychological Strain

Abstract: Workplace bullying is regarded as one of the most devastating stressors at work for those targeted, and the bullying-mental health relationship is well-documented in the literature, even under lower levels of exposure. However, less is known about when and for whom these negative behaviors have more effect. Perceived control over outcomes in life (i.e., internal locus of control) has normally been related to good health and well-being, while relying on chance and/or powerful others (i.e., external locus of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 62 publications
(95 reference statements)
2
38
0
5
Order By: Relevance
“…There is a wide agreement that workplace bullying is a serious work environment problem that has severe consequences for the exposed ( Nielsen and Einarsen, 2012 , 2018 ; Arenas et al, 2015 ; Nauman et al, 2019 ; Nielsen et al, 2019 ; Reknes et al, 2019 ). However, there is less agreement about the causality, the process, and possible moderators and mediators ( Nielsen and Einarsen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide agreement that workplace bullying is a serious work environment problem that has severe consequences for the exposed ( Nielsen and Einarsen, 2012 , 2018 ; Arenas et al, 2015 ; Nauman et al, 2019 ; Nielsen et al, 2019 ; Reknes et al, 2019 ). However, there is less agreement about the causality, the process, and possible moderators and mediators ( Nielsen and Einarsen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a wider perspective, numerous cross-sectional and prospective studies show that individual dispositions, which are traditionally associated with protective and coping-enhancing factors, are less beneficial than might be expected when targets are exposed to high levels of bullying behaviors over time [9]. It is suggested that this is due to loss of control [40], which simultaneously impedes the victim's basic need for autonomy. This line of argument is supported by findings showing that exposure to bullying behavior threatens the satisfaction of an individual's basic psychological needs [17] and frustrates their need satisfaction [44].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of workers who were exposed to low levels of bullying behaviors at the workplace, hardiness was a protective factor in the bullying-anxiety relationship, yet did not moderate the bullying-depression relationship [37]. However, a range of studies have lately shown that individual dispositions that are similar to hardiness, such as sense of coherence [38], the ability to defend [39], internal locus of control [40], and problem-focused strategies [41], do not protect targets when facing bullying the way they are supposed to do theoretically [9]. In summary, these studies show that individual resources, such as hardiness, only have a protective effect in cases of low exposure to bullying behaviors at the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…To address this limitation, we draw on attribution theory, a central tenet of which is that individuals have a need to identify the causal agents of significant aspects of their lives because doing so serves to defend or enhance self-esteem, public identity, and/or positive emotions ( Shepperd, Malone, & Sweeny, 2008 ). Within attribution theory research, locus of control has emerged as an important moderator of individuals’ affective and behavioral responses to stressors (e.g., Debus et al, 2014 , Jiang et al, 2020 , Reknes et al, 2019 ). Consistent with these studies, our model incorporates locus of control as a moderator of the relationship between consumer confidence and perceived financial vulnerability.…”
Section: Hypotheses Developmentmentioning
confidence: 99%